Innovative Approach to Solving Theoretical Issues of the Ecological and Epidemiological Concept of Sapronoses - A. B. Belov (Эпидемиология и вакцинопрофилактика, 2018)
The history of the study of infections attributed by the microbiologist and epidemiologist V.I. Tersky in 1958 as the class of human infectious diseases – «Sapronoses» is presented. Over the past 60 years in the world and especially in Russian science the knowledge that allows us to complete the development of an ecological and epidemiological theory of sapronoses infections was accumulated. This knowledge should be extended to the whole complex of biomedical sciences associated with the population pathology of biota. To solve the controversial and complex issues of the theory, terminology and classifications of population infectology, it is necessary to integrate the knowledge of specialists in various fields of research and practice in the medicine, veterinary medicine, parasitology, phytopathology and other disciplines. The ways and prospects of improving the general theory of infectology in the light of new approaches to understanding the essence of sapronoses are discussed.